IMPLEMENTATION OF THE INTEGRATION OF CHARACTER VALUES IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT MADRASAH ALIYAH - Syakir Munandar, Didih (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Character education plays a crucial role in shaping the moral foundation of a nation, influencing the quality of human resources. In the context of Islamic Religious Education (IRE), the integration of character values is essential to nurturing ethical behavior among students. Purpose: This research explores the implementation of character values integration into IRE at Madrasah Aliyah. Method: Employing a qualitative descriptive research methodology, this study identifies the collaborative efforts required from all components of the madrasa, including the principal, teachers, and educational staff, to successfully integrate character values into the learning process. Result: The findings indicate that the integration process requires comprehensive support from all stakeholders to ensure optimal internalization of character values. Conclusion: The study concludes that the integration of character education within IRE is most effective when supported by adequate facilities and institutional cooperation, leading to a more holistic development of students' character.